2019
DOI: 10.3390/ijerph16234812
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Long-Term Outcomes of Organisational Health Literacy Interventions in Ireland and The Netherlands: A Longitudinal Mixed-Methods Study

Abstract: Organisational Health Literacy (OHL)-interventions are needed to overcome health inequality. OHL-interventions have successfully identified communication barriers at the organisational level, but evidence is limited on the extent to which this leads to sustainable organisational change. This study aims to assess the implementation fidelity, moderators (barriers and facilitators), and long-term impact of OHL-interventions in hospitals in Ireland and The Netherlands. We used a longitudinal mixed-methods approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 38 publications
3
63
0
Order By: Relevance
“…This might, for instance, be achieved by health care professionals actively distributing such materials, or by simply placing multiple displays throughout the waiting room. In addition, other methods can be used to better tailor healthcare delivery to the needs of patients with low levels of health literacy, for instance by strengthening the skills of health care professionals to communicate with these patients [ 47 , 48 ], or by adapting the organization and design of health care services [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might, for instance, be achieved by health care professionals actively distributing such materials, or by simply placing multiple displays throughout the waiting room. In addition, other methods can be used to better tailor healthcare delivery to the needs of patients with low levels of health literacy, for instance by strengthening the skills of health care professionals to communicate with these patients [ 47 , 48 ], or by adapting the organization and design of health care services [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trezona et al [64] provide a relevant self-assessment tool for organizational health literacy in "Field-Testing and Refinement of the Organisational Health Literacy Responsiveness Self-Assessment (Org-HLR) Tool and Process". Kaper et al [65] consider the sustainable changes and longitudinal outcomes of organizational health literacy efforts in "Implementation and Long-Term Outcomes of Organisational Health Literacy Interventions in Ireland and The Netherlands: A Longitudinal Mixed-Methods Study". As in many studies, this considers two different health contexts and the need to address health inequality.…”
Section: Organizational Level: Health Systemsmentioning
confidence: 99%
“…Together with the assessment, these studies also often evaluated the feasibility of the OHL-instrument. Eleven studies reported on both the assessment and on findings regarding the planning and delivery of interventions [22,[25][26][27][28][29][30][31][32][33][41][42][43]. Fourteen studies were conducted in the United States [22][23][24]28,29,[31][32][33][34]36,[38][39][40]43]; other studies were conducted in Australia [25][26][27]30,41], New Zealand & Canada [37], and several European countries including Austria [35], Italy [17], Ireland and the Netherlands [42], and Spain [3].…”
Section: Description Of Studiesmentioning
confidence: 99%